2021
DOI: 10.3390/ijms222111768
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and α-Tocopherol Enhance the Protective Effect of Each Other on Brain Cortical Neurons under Oxidative Stress Conditions and in Rat Two-Vessel Forebrain Ischemia/Reperfusion Injury

Abstract: Clinical trials show that insulin administered intranasally is a promising drug to treat neurodegenerative diseases, but at high doses its use may result in cerebral insulin resistance. Identifying compounds which could enhance the protective effects of insulin, may be helpful to reduce its effective dose. Our aim was thus to study the efficiency of combined use of insulin and α-tocopherol (α-T) to increase the viability of cultured cortical neurons under oxidative stress conditions and to normalize the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…It is known that tocopherol and tocotrienol compounds prevent lipid peroxidation due to their ROS scavenger properties [ 44 ], protecting unsaturated fatty acids and lipid mediators [ 31 ]. In addition, α-tocopherol regulates the expression of genes implicated in apoptosis or antioxidant defenses, such as Bcl2-L1 or γ-glutamylcystein synthetase [ 44 , 45 ], or in lipid homeostasis, such as phospholipase A2 [ 46 ], which has 1-O-acyl ceramide synthase activity, using ceramides as an acceptor [ 47 ]. Thus, we predicted that lipid changes due to Paraquat exposure can be mitigated by this antioxidant pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that tocopherol and tocotrienol compounds prevent lipid peroxidation due to their ROS scavenger properties [ 44 ], protecting unsaturated fatty acids and lipid mediators [ 31 ]. In addition, α-tocopherol regulates the expression of genes implicated in apoptosis or antioxidant defenses, such as Bcl2-L1 or γ-glutamylcystein synthetase [ 44 , 45 ], or in lipid homeostasis, such as phospholipase A2 [ 46 ], which has 1-O-acyl ceramide synthase activity, using ceramides as an acceptor [ 47 ]. Thus, we predicted that lipid changes due to Paraquat exposure can be mitigated by this antioxidant pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a significant number of studies on the effects of peripheral and intracerebroventricular insulin administration to correct the consequences of cerebral ischemia, there are relatively few data on the use of INI, despite the promise of this method for correcting ischemic damage [ 186 , 187 , 188 , 189 , 190 , 191 , 192 ]. It should be noted that intranasally administered IGF-1 has been used for the correction of damage caused by cerebral ischemia–reperfusion for 20 years [ 186 , 193 , 194 , 195 , 196 , 197 , 198 , 199 ].…”
Section: Intranasal Insulin and Brain Ischemiamentioning
confidence: 99%
“…In 2018–2022, we carried out a set of studies on the ability of INI to influence metabolic processes and oxidative stress during bilateral global forebrain ischemia-reperfusion in rats [ 187 , 188 , 189 , 190 ]. At doses of 0.25 and 0.5 IU/rat, INI showed antioxidant and neuroprotective effects on the brain of rats with ischemia, and also prevented oxidative inactivation of Na + /K + -ATPase and accumulation of lipid peroxidation (LPO) products in the brain.…”
Section: Intranasal Insulin and Brain Ischemiamentioning
confidence: 99%
“…Zakharova et al 62) also investigated the efficacy of combining insulin and α-tocopherol to increase the viability of cultured cortical neurons under oxidative stress conditions and to normalize metabolic disturbances caused by free radical reaction activation in rats with two-vessel forebrain ischemia/reperfusion injury in the brain cortex. The latter demonstrated that α-tocopherol improved the protective and antioxidative actions of insulin on neurons.…”
Section: Tocopherolsmentioning
confidence: 99%